Dental age estimation in a Brazilian adult population using Cameriere's method - Alana de Cássia Silva AZEVEDO; Nathalia Zanini ALVES; Edgard MICHEL-CROSATO; Marcos ROCHA; Roberto CAMERIERE; Maria Gabriela Haye BIAZEVIC (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objectives of this study were to develop a specific formula to estimate age in a Brazilian adult population and to compare the original formula from Cameriere to this Brazilian formula. The sample comprised 1,772 periapical radiographs from 443 subjects (219 men, 224 women) that were organized into 12 groups according to sex (men or women) and age (20-29, 30-39, 40-49, 50-59, 60-69, and 70 years and older). The films were analyzed using the criteria described by Cameriere et al. (2004) and Adobe Photoshop®. We obtained a mean error of 8.56 (SD = 5.80) years for tooth 13, 7.99 (SD = 5.78) years for tooth 23, 8.38 (SD = 6.26) years for tooth 33, and 8.20 (SD = 6.54) years for tooth 43. When teeth were combined in the analysis, we observed lower mean errors. The Brazilian formula developed from this sample group was more accurate than Cameriere's formula. However, other factors must be considered to improve age estimates in adults.